The Investigation of Critical Thinking Dispositions of Religious Culture and Ethics Teacher Candidates - Abdulkadir Cekin (Journal of Education and Learning (EduLearn), 2015)
The purpose of this study is to investigate the critical thinking dispositions of religious culture and ethics teacher candidates in terms of some variables. The independent variables of the study are gender, high school types from which they graduated, birth place, motherland, education level of their parents, and family’s average income. The sample of the study is 226 teacher candidates in Ankara University and Kastamonu University, religion culture and ethics teaching department. The research is designed as a case study; the data is obtained by Measurement of California Critical Thinking Disposition Inventory. The inventory is a lykert-type scale, has 51 items. The value of the overall reliability of measurement instrument (Cronbach Alpha) is 0.88. A one way analysis of variance (ANOVA) and independent samples t-test are used to analyze the data. In the end of the study, it was found that religious culture and ethics teacher candidates think sufficiently critical.